Determining and comparing the achieved competencies of graduating nursing students of public and private universities in Iran - Majid Purabdollah; Vahid Zamanzadeh; Akram Ghahramanian; Leila Valizadeh; Mostafa Ghasempour; Saeid Mousavi (BMC Medical Education)
Abstract Aim This study aims to determine and compare the achieved competencies of graduating nursing students of public and private universities in Iran. Background The main responsibility of nursing education is to train nurses who possess the necessary competencies to provide safe and high-quality care. Given that a significant proportion of nursing education in Iran is the responsibility of private universities, it is essential to ensure that nursing graduates acquire the required competencies. Design and methods A quantitative study with a comparative descriptive design was conducted. A convenience sample of 721 graduating nursing students, including 301 from private universities and 420 from public universities, participated in the study. Data was collected using a nursing competence questionnaire developed in the Iranian cultural context and rated on a 5-point Likert scale (1 = dependent to 5 = independent). The research findings were analyzed using descriptive statistics and the independent t-test. Results The students from public and private universities achieved the highest scores in work readiness and professional development, with means of 3.58 (SD = 0.39) and 3.48 (SD = 0.37), respectively. The lowest scores were obtained by both the public and private groups for evidence-based care, with means of 2.89 (SD = 0.54) and 2.54 (SD = 0.50), respectively. The mean score of core competence obtained by public nursing students across all 5 themes was higher than that of private students, and this difference was statistically significant (p < .05). The evidence-based nursing care showed the greatest difference in means (mean difference = 0.35), while individualized care had the smallest difference (mean difference = 0.09) according to the results of the independent t-test. Conclusion Neither public nor private university nursing students achieved an independent level in any of the competencies. However, public university students demonstrated greater success in acquiring most of the competencies compared private students. To enhance nursing students’ competencies, future studies should focus on developing operational solutions, particularly for students at private universities.